Keadilan sosial dalam sistem masyarakat menurut Mustafa Al-Siba‘I - Mohd Hatib Ismail,; Siti Rohani Jasni,
Justice is the main thing in the formation of a prosperous social system. Social defects from economic, political, and educational aspects often occur when social justice is neglected. In the vibrancy of Western and Islamic scholars discussing the theory and idea of social justice, Mustafa al-Siba'i (1915-1964) was also involved in examining the matter in the formation of social systems in society. This study aims to explain the concept of social justice according to Mustafa al-Siba'i from the point of view of individual rights, responsibility, and social welfare. This study uses descriptive content analysis as an approach to analyzing Mustafa al-Siba'i works on social justice. The results found that Mustafa al-Siba'i emphasized the issue of fundamental rights for each individual should be preserved and protected in upholding justice. Every person has their own rights and is also responsible for giving rights to others. In addition, Mustafa al-Siba'i also outlined general guidelines for managing the national treasury based on Islamic principles and gave some examples of management established by previous Islamic governments. Regarding social welfare, Mustafa al-Siba'i presented a concept that already exists in Islam, namely helping each other, defending weak people, and sharing wealth and responsibilities among the community. This study is expected to give the community an understanding of the concept of social justice that exists in Islam through the thinking of Mustafa al-Siba'i.